MOVES WITHIN THE LITERATURE REVIEWS AND DISCUSSION SECTIONS OF INTERNATIONAL POSTGRADUATE THESES AND DISSERTATION ON ELT AND APPLIED LINGUISTICS - Fuad Abdullah (Institut Pendidikan Indonesia Garut, 2018)
Literature Reviews (LRs) and Discussion sections are plausibly considered as indispensable components in theses and dissertations. To illustrate, LRs commonly function to rationalize the value of the research and to delineate its differences with what has been authenticated in the existing literature. Meanwhile, Discussion sections enable the writers to answer the research questions, summarize findings or focus on the primary findings. Conversely, there is a dearth of research on LRs and Discussions from a genre-analytic perspective. To fill this void, this study aimed at exploring the obligatory, conventional, and optional moves in the LRs and Discussions of a number of postgraduate theses and a dissertation on ELT and Applied Linguistics. The data were collected through document analysis by involving three MA theses and one dissertation as the corpus of this study (N=4). The data were analyzed by following the concepts of Jian’s Schematic Structure on LRs (Jian, 2010) and Nodoushan & Khakbaz’s Rhetorical Moves of Discussion sections (Nodoushan & Khakbaz, 2011). The findings displayed that Establishing territory (Move 1), Surveying & summarizing previous research (Move 2) and Creating a research niche (Move 3) can probably categorized as important and obligatory moves to exist in LRs. Furthermore, Reporting results (Move 2), Commenting on results (Move 4), Evaluating study (Move 6) & Deductions from research (Move 7) are obviously assumed to be obligatory for they can cover the essence of other moves in Discussion sections. Therefore, move-sensitivity should be implanted and developed earlier to help students write effective and informative LRs and Discussion sections both within postgraduate theses and dissertations